Institutional experience using interstitial brachytherapy for the treatment of primary and recurrent pelvic malignancies - Aridgides, Paul; Onderdonk, Benjamin; Cunningham, Mary; Daugherty, Emily; Du, Lingyun; Bunn, W. Douglas; Agarwal, Rinki; Hahn, Seung Shin (Journal of Contemporary Brachytherapy, 2016)
Purpose: The study assessed the outcomes of patients at a single institution with locally advanced primary and recurrent pelvic malignancies treated with interstitial high-dose-rate (HDR) or low-dose-rate (LDR) brachytherapy (BT), using a modified Syed-Neblett template. Material and methods : Between 1996 and 2010, 60 patients with primary or recurrent pelvic malignancies were treated with interstitial BT. Thirty three patients had primary malignancies with 6.1% being stage I, 33.3% stage II, 45.5% stage III, and 15.2% stage IV; the remaining 27 patients were recurrent malignancies. Fifty four patients received external beam radiotherapy (EBRT) as part of their treatment course. The median EBRT, BT, and EBRT + BT doses were 45 Gy, 20 Gy, and 65 Gy, respectively. Thirty eight patients received concurrent chemotherapy with EBRT. Complete response (CR) was defined by absence of clinical and radiographic disease on first follow-up. Toxicity was graded as per Common Terminology Criteria for Adverse Events, version 4.0. Results : The median follow-up was 37 months (4-234 months) and initial CR was achieved in 91%. For primary cancers at diagnosis, 5-year local control (LC), 5-year progression-free survival (PFS), 5-year overall survival (OS) were 65%, 64%, and 42% respectively. For recurrent cancers at diagnosis, 5-year LC, 5-year PFS, and 5-year OS were 80%, 51%, and 37%, respectively. There was a significant difference in both OS and PFS among different tumor sites (p < 0.05), with vaginal cancers having the best 5-year OS (55%) and PFS (84%). There was a total of 1 acute toxicity ≥ grade 3, 6 late grade 3 toxicities, and late grade 4 toxicity. Conclusions : Our series suggests that interstitial BT using a modified Syed-Neblett template is a safe and effective treatment for primary or recurrent pelvic malignancies. This technique allowed effective LC and 97% of patients had preservation of both bladder and rectal function.